EXPLORING AGE AND GENDER DIFFERENCES IN NARCISSISM AND PERFECTIONISM AND THEIR MENTAL-HEALTH CORRELATES - KÁLLAY, Éva; MIHOC, Alexandra Rebeca (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2021)
The changes occurring in modern society can significantly influence individuals’ well-being, mental health and even personality traits such as narcissism and perfectionism. Since studies investigating age and gender differences in narcissism and perfectionism have produced mixed results, and the number of studies conducted in Romanian population is scarce, the main aims of this study were to investigate possible age and gender differences in narcissism, perfectionism and several mental-health indicators in a sample of healthy participants, as well as specific association patterns between these variables within each group of participants. Our sample included 465 millennials and 149 participants over 35 years of age. The results indicate that millennials reported significantly lower levels of narcissism and self-oriented perfectionism than the older generations, higher levels of depressive symptoms and lower levels of autonomy, environmental mastery, purpose in life, and self-acceptance. Female millennials reported lower levels of narcissistic traits and higher levels of socially-prescribed perfectionism, depressive symptoms, personal growth, and positive relations with others than male participants. Older females indicated significantly higher levels of depressive symptoms and loneliness than male participants. Regarding association patterns, in the group of millennial women narcissism was positively correlated with self-oriented, socially-prescribed perfectionism and subjective well-being, and negatively with loneliness, environmental mastery and purpose in life. In millennial males, we found significant positive correlations only between narcissism and subjective well-being and environmental mastery. Our findings may have important implications for the literature regarding millennials and can contribute to the interventions and prevention programs designed to improve their well-being.